Test-retest reliability of Malay version of stroke knowledge test - Sowtali, Siti Noorkhairina; Ghazali, Norhasyimah; Mohd Yusoff, Dariah; Harith, Sakinah; Mohamed, Monniaty; Ishak, Nur' Ain (IIUM Press, 2019)
Objective: This study was aimed to evaluate the stability and reliability of the Malay version of the Stroke Knowledge Test among kidney disease patients at the Hemodialysis Unit and Nephrology Clinic of Hospital Tengku Ampuan Afzan, Kuantan. Methods: A cross-sectional study was conducted on 30 conveniently selected kidney disease patients between April and May 2017. The questionnaires consisted of three parts: sociodemographic background, clinical, and lifestyle-related risk factors; the Malay version of the Stroke Knowledge Test were administered on the patients in a pre-test/post-test manner with a gap of two weeks. Results: The Malay version of the Stroke Knowledge Test had a fair pre-test/post-test agreement (ICC=0.247) when administered on the kidney disease patients to measure their knowledge of stroke. The items were considered to have acceptable difficulty and discrimination indexes. They were also reliable as all aspects of stroke were covered. Conclusions: The Malay version of the Stroke Knowledge Test had a fair pre-test/ post-test agreement when conducted on the kidney disease patients to check its stability and reliability. The results reflected a mixture of easy and moderate content, as well as acceptable modifications of the items. Hence, as per previous researches, this instrument was considered to be a reliable tool for evaluating the knowledge of stroke outcomes in kidney